Pembuatan dan Pemanfaatan Larutan Multiguna Eco Enzyme sebagai Upaya Reduksi Limbah Organik di Kampoeng Kuliner Makassar: Production and Aplication of Eco Enzyme Multipurpose Solutions as an Effort for Organic Waste Reduction of Kampoeng Kuliner Makassar - Andi Zulfikar Syaiful; Muh. Fikruddin; Ridwan Ridwan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Kampoeng Kuliner Makassar (KKM) is one of the MSMEs in the culinary field in Makassar. KKM produces about 25 kg/day of organic waste, mainly fruit and vegetable. This community partnership program is a form of transfer of knowledge and technology fermentation in organic waste treatment, which aims to assist KKM partners in processing fruit and vegetable peel waste into eco-enzyme which is then used as a multipurpose cleaning solution according to KKM needs. This activity consists of a focus discussion group (FGD), counseling, making and harvesting eco enzyme, and its application in the restaurant as a multipurpose cleaning solution. Paired t-test results of participants' pre-test and post-test showed a significant increase (p-value < 0.001) in participants' knowledge about various aspects of eco-enzyme. The participants' skills are improved through independent practice so that all participants can produce good quality eco enzymes. Eco-enzyme has been used as a cleaning and disinfection agent, such as washing agents for food, tableware, and cooking utensils; kitchen and bathroom cleaners at KKM. After this community partnership program, it is hoped that KKM can become a place to promote a healthy lifestyle with minimal waste.